Control fiscal del programa ingreso solidario covid 19 en Colombia - Espitia Salas, Doris Magaly (Universidad Antonio Nariño, 2021)
The content of this article reveals a simple descriptive methodology. It presents an analysis of fiscal control in Colombia for cases of States of Economic, Social and Ecological Emergencies. It takes a special